New antimalarials identified by a cell-based phenotypic approach: Structure–activity relationships of 2, 3, 4, 9-tetrahydro-1H-β-carboline derivatives possessing a 2-((coumarin-5-yl)oxy)alkanoyl moiety. (15th July 2022) - Cho, Nobuo; Kikuzato, Ko; Futamura, Yushi; Shimizu, Takeshi; Hayase, Hiroki; Kamisaka, Kikuko; Takaya, Daisuke; Yuki, Hitomi; Honma, Teruki; Niikura, Mamoru; Kobayashi, Fumie; Watanabe, Nobumoto; et al.
Graphical abstract: Abstract: The identification, structure–activity relationships (SARs), and biological effects of new antimalarials consisting of a 2, 3, 4, 9-tetrahydro-1 H -β-carboline core, a coumarin ring, and an oxyalkanoyl linker are described. A cell-based phenotypic approach was employed in this search for novel antimalarial drugs with unique modes of action. Our screening campaign of the RIKEN compound library succeeded in the identification of the known tetrahydro-β-carboline derivative (4e ) as a hit compound showing significant in vitro activity. SAR studies on this chemical series led to the discovery of compound 4h having a ( R )-methyl group on the oxyacetyl linker with potent inhibition of parasite growth (IC50 = 2.0 nM). Compound 4h was also found to exhibit significant in vivo antimalarial effects in mouse models. Furthermore, molecular modeling studies on 4e, 4h, and its diastereomer (4j ) suggested that the ( R )-methyl group of 4h forces the preferential adoption of a specific conformer which is considered to be an active conformer.